I was just watching session 2 Clip 2, where the professor solves for the area of the triangle formed by any tangent line to y = 1/x and the y- and x-axes. While he finds the x-intercept of the tangent in a straightforward manner, using the equation y - y0 = -(1/(x0)^2) * (x - x0), from the fact that the derivative of y = 1/x is y = -1/x0^2, making the equation of a tangent line to y = 1/x at some point (x0,y0) what I listed above in point-slope form. But when finding the y-intercept, he takes a shortcut using the fact that y = 1/x is its own inverse function. Can anyone explain this shortcut
OCW Scholar - Single Variable Calculus
Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga.
Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus.
Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
If you rename x to y and y to x, you end up with the same form of equation, and that equation will have the same value for its intercept (but for x).
Let me use an example in physics to explain inverse function:
We know a formula that converts F temperature to C temperature
C = 5/9 (F-32)
To find C, what we do is subtract 32 from F and then multiply by 5/9.
To find F, we have to reverse the process.
Multiply C by 9/5 and then add 32.
Therefore, F = (9/5 * C) +32
Similarly, the inverse function of y = 1/x is x =1/y (replacing y with x and x with y)
Now, you know the equation of the tangent line as y-1/xo = -1/xo^2 (x-xo)
Interchange x and y, xo and yo
Plugging the value y=0, you get y = 2yo
In simple words, if y= 1/x you get x=2xo. If x = 1/y you get y = 2yo
Hope you understand this.